2020
DOI: 10.1055/a-1261-3349
|View full text |Cite
|
Sign up to set email alerts
|

Novel polyp detection technology for colonoscopy: 3D optical scanner

Abstract: Background and study aims Fifty-eight percent of American adults aged 50 to 75 undergo colonoscopies. Multiple factors result in missed lesions, at a rate of approximately 20 %, potentially subjecting patients to colorectal cancer. We report on use of a miniaturized optical scanner and accompanying processing software capable of detecting, measuring, and locating polyps with sub-millimeter accuracy, all in real time. Materials and methods A prototype 3 D optical scanner was developed that fits within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
(13 reference statements)
0
1
0
1
Order By: Relevance
“…It was estimated that approximately 9%-27% of polyps/adenomas were overlooked during the conventional 2D colonoscopy procedure (5,6). In this circumstance, the 3D imaging technology was introduced to improve the PDR and ADR by highlighting the morphological characteristics of lesions, thereby providing assistance for lesion identification (10)(11)(12)(13)(14). Prior evidence indicated that 3D imaging devices could not only increase the contrast between lesions and adjacent mucosa in real time but also did not prolong the operation time (14).…”
Section: Discussionmentioning
confidence: 99%
“…It was estimated that approximately 9%-27% of polyps/adenomas were overlooked during the conventional 2D colonoscopy procedure (5,6). In this circumstance, the 3D imaging technology was introduced to improve the PDR and ADR by highlighting the morphological characteristics of lesions, thereby providing assistance for lesion identification (10)(11)(12)(13)(14). Prior evidence indicated that 3D imaging devices could not only increase the contrast between lesions and adjacent mucosa in real time but also did not prolong the operation time (14).…”
Section: Discussionmentioning
confidence: 99%
“…Разработена е нова технология за колоноскопско откриване на колоректални полипи, включваща прототип на миниатюризиран триразмерен оптически скенер с големина на стандартен ендоскоп и компютърна програма за откриване, измерване и локализиране на полипи в реално време с точност под 1 mm (15). Средното разстояние между две съседни точки в триразмерния облак възлиза на 94 µm.…”
Section: обсъжданеunclassified